Uptake of Heavy Metal Ions by Carbonaceous Material Obtained from Industrial Waste Lignin Using Microwave Irradiation - R. Chaudhari, Archana; P. Nagpurkar, Laxman; D. Ekhe, Jayant (Asian Journal of Chemistry, 2010)
Lignin is a major waste material from the pulp and paper industries. Its lesser utilization and disposal problems make it a matter of environmental concern. Therefore, in such a case, greater and better utilization is the key to minimize the waste, that too for the treatment of waste waters. In the present studiy, the microwave irradiation, zinc chloride and subsequent treatment have been utilized. It produced a good yield of carbonaceous solid material having good capacity to uptake the toxic metal ions from aqueous solutions. Uptake studies have been undertaken on toxic metal ions, viz., Cu2+, Ni2+, Cr6+, Pb2+, Zn2+, Cd2+, As3+ and Hg2+, etc. Interestingly, the exahausted material may also be used as a solid fuel supplement due to its high calorific value, 5400 kcal/kg.